2020
DOI: 10.1136/bmjgh-2019-001915
|View full text |Cite
|
Sign up to set email alerts
|

What the percentage of births in facilities does not measure: readiness for emergency obstetric care and referral in Senegal

Abstract: IntroductionIncreases in facility deliveries in sub-Saharan Africa have not yielded expected declines in maternal mortality, raising concerns about the quality of care provided in facilities. The readiness of facilities at different health system levels to provide both emergency obstetric and newborn care (EmONC) as well as referral is unknown. We describe this combined readiness by facility level and region in Senegal.MethodsFor this cross-sectional study, we used data from nine Demographic and Health Surveys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…Likewise, women are frequently transferred out of the private sector to government facilities when complications arise, or when fetal death is diagnosed. Reducing stillbirths in government facilities will not only require improvements in the quality of care delivered at the facility, but also strengthening the referral pathways from lower level or private facilities to ensure that women and their babies receive timely emergency interventions if required [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, women are frequently transferred out of the private sector to government facilities when complications arise, or when fetal death is diagnosed. Reducing stillbirths in government facilities will not only require improvements in the quality of care delivered at the facility, but also strengthening the referral pathways from lower level or private facilities to ensure that women and their babies receive timely emergency interventions if required [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Looking at the geographic accessibility during inter health facility referral, the median distance between health facilities that can(not) perform caesareans section was 32km (ie, 41-minute driving time) in Senegal [ 63 ]. On the contrary, in two regions of Ethiopia (Tigray and Amhara), the average time between the two facilities was as high as two hours [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Senegal, we also excluded health huts, as the assessment instrument differ for these single-room facilities and did not record elements of process quality of care. However, health huts are often in the front-line in the management of sick children in remote rural areas and studying their referral practices to larger health facilities would be an important undertaking (Cavallaro et al ., 2020). Second, we estimated process quality metrics from survey instruments using two different assessment methods (direct observation of consultations vs clinical vignettes), although previous studies have shown that there is a difference between what health providers know and what they do (Peabody et al ., 2000; Leonard and Masatu, 2005).…”
Section: Discussionmentioning
confidence: 99%